Design and Development of College Archives and Correspondence Applications - Husna, Meryatul; Lukcyhasnita, Andam; Sembiring, Ajulio Padly; Faza, Sharfina; Andriyani, Poppy (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
This study aims to develop a web-based archiving and correspondence application to improve the efficiency and effectiveness of archiving and delivery of correspondence on the smart campus. The method used is the software development method. This research involves data collection through interviews and observations to understand the process of archiving and delivering correspondence on smart campus. The developed application can help users to archive and deliver correspondence more efficiently and effectively with features such as correspondence search, automatic archiving, and task and notification settings. The results showed that the use of web-based archives and correspondence applications can increase the efficiency and effectiveness of archiving and delivering correspondence on smart campuses by reducing time and costs, and increasing the accuracy and security of correspondence and archive management.